A comparison of computational models for the extracellular potential of neurons - Pods, Jurgis (Journal of integrative neuroscience, 2017)
The extracellular space has an ambiguous role in neuroscience. It is present in every physiologically relevant system and often used as a measurement site in experimental recordings, but it has received subordinate attention compared to the intracell